Influence of Type and Concentration of Acids on Hydrolisis Starch of “Taro Tuber” Into Sugar Liquid - Amna Hartiati; I.A Mahatma Tuningrat (APTA and DTIP FTP UGM, 2020)
The objectives of this research are (1) to know the effect of acid type and concentration on the hydrolysis of Taro tuber starch into liquid sugar (2) to know the type and concentration of acid that can produce the best liquid sugar characteristic in the hydrolysis of Taro tuber starch. The study used a complete randomized design with two factorial patterns. There are the type and concentration of acid used for the hydrolysis of Taro tuber starch. The variables observed were sugar reduction and liquid sugar clarity. The results showed that the type and concentration of acids and their interactions significantly affected the Dextrose Equivalent of liquid sugar produced. The best treatment is hydrolysis using nitric acid (HNO3) with 6% concentration with Dextrosa Equivalent is 57,470 %.